Assessment of structural knowledge in pulmonary physiology of first year medical students using case narratives at Pamantasan ng Lungsod ng Maynila - Jocson, Raquel C. (2000)
This study implemented small group learning using case narratives to first year medical students at Pamantasan ng Lungsod ng Maynila, in the study of pulmonary physiology and assessed the students' structural knowledge attained during the learning activity. Four case narratives were designed, revised after review by physiology teachers of medical schools and implemented in small group discussion. Two groups of students (10 each group) were observed. They constructed concept maps on the case narratives. The similarity between students' and teachers? concept maps was determined using Closeness © measure and pathfinder scaling algorithm. Results of C-measures are: 0.95 and 0.91; 0.82 and 0.69; 0.81 and 0.90 and 0.90 for case narratives 1,2,3 and 4 respectively. C value of 1 signifies that the concept maps are identical. In pathfinder scaling logarithm, the distance between concepts was measured and correlation of similarity between teacher's and students' concept maps was determined. Correlation coefficients are: 0.84 and 0.87; 0.90 and 0.55; 0.77 and 0.97; 0.75 for case narratives 1,2,3 and 4 respectively. Correlation values are all above 0.5 signifying significant correlation. The students were able to perceive the cognitive benefits cited in the literature. In conclusion, students' knowledge developed through problem-based learning can be quantitatively evaluated using concept mapping. Small group discussion can produce outcomes very close to what the teachers intended to happen during the learning process.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Case Method Teaching; Small groups